Activating the Benefit of Diversity Through Team Role Clarity and Implicit Coordination. (August 2021) - Chen, Shuai; Wang, Weiliang; Cheng, Jialin; Teng, Da
Over the last several decades, studies on the relationship between task knowledge diversity and team performance have yielded mixed findings. Extending past studies, we propose that the impact of task knowledge diversity on team performance is dependent on the level of team role clarity and implicit coordination. This study, based on two-wave time-lagged data from 62 teams comprising 336 individuals, provided support for the proposed model and showed that team role clarity and implicit coordination moderate the relationship between task knowledge diversity and team performance. Overall, task knowledge diversity has a positive effect on team performance when either team role clarity or implicit coordination is high, and this effect is even stronger when both are high.